2010
DOI: 10.1519/jsc.0b013e3181ddb03d
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Muscular Strength in Youth: Usefulness of Standing Long Jump as a General Index of Muscular Fitness

Abstract: The purpose of the present study was to examine the association among different measures of lower body muscular strength in children, and the association between measures of lower- and upper-body muscular strength. The study population comprises 94 (45 girls) healthy Caucasian children aged 6-17 years. Children performed several lower body explosive muscular strength tests (i.e., standing long jump [SLJ], vertical jump, squat jump, and countermovement jump) and upper body muscular strength tests (i.e., throw b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
252
1
25

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 327 publications
(289 citation statements)
references
References 25 publications
11
252
1
25
Order By: Relevance
“…12,13 In brief, cardiorespiratory fitness was assessed by the 20-meter shuttle-run test, 14 and maximum oxygen consumption (VO 2max , mL/kg/min) was estimated by using the equation reported by Léger et al 14 Muscular fitness was assessed by means of the handgrip strength [15][16][17] and standing long-jump 16,18 tests. Speed-agility was assessed with the 4310-meter shuttlerun test.…”
Section: Physical Fitnessmentioning
confidence: 99%
“…12,13 In brief, cardiorespiratory fitness was assessed by the 20-meter shuttle-run test, 14 and maximum oxygen consumption (VO 2max , mL/kg/min) was estimated by using the equation reported by Léger et al 14 Muscular fitness was assessed by means of the handgrip strength [15][16][17] and standing long-jump 16,18 tests. Speed-agility was assessed with the 4310-meter shuttlerun test.…”
Section: Physical Fitnessmentioning
confidence: 99%
“…Recently published researches in girls at the age of 6 -17 years also indicate a strong connection between the standing long jump and other tests for assessment of the strength abilities [20]. The standing long jump test is a very practical, time efficient and cheap method of assessing the muscular fitness in children and adolescents in school conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of Brazilian students aged 7 -15 showed that the single SLJ could possibly reflect the overall fitness level indicated by other muscular tests such as the 1-minute curl-up, pull-up, ball throw, 9-minute run, 20-meter run and 4-meter shuttle run [5]. Recent studies of healthy Caucasian girls aged 6 -17 have also indicated a strong association between the SLJ and other lower-body muscular strength tests [6]. Indeed, SLJ tests can be practical, time-efficient and affordable methods for assessing muscular fitness in young children.…”
Section: Introductionmentioning
confidence: 99%